2012
DOI: 10.1038/aps.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo investigation of dexibuprofen derivatives for CNS delivery

Abstract: Aim: Dexibuprofen, the S(+)-isomer of ibuprofen, is an effective therapeutic agent for the treatment of neurodegenerative disorders. However, its clinical use is hampered by a limited brain distribution. The aim of this study was to design and synthesize brain-targeting dexibuprofen prodrugs and to evaluate their brain-targeting efficiency using biodistribution and pharmacokinetic analysis. Methods: In vitro stability, biodistribution and pharmacokinetic studies were performed on male Sprague-Dawley rats. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…This is consistent with our previous study of brain targeting by these prodrugs. 18 Uptake characteristics were different for the prodrugs. Uptake of DIBU and of prodrugs III and IV increased linearly with incubation time and concentrations, it did not differ significantly between 37°C and 4°C, and it was not inhibited by sodium azide or rotenone.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with our previous study of brain targeting by these prodrugs. 18 Uptake characteristics were different for the prodrugs. Uptake of DIBU and of prodrugs III and IV increased linearly with incubation time and concentrations, it did not differ significantly between 37°C and 4°C, and it was not inhibited by sodium azide or rotenone.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13], in human serum and other physiologic fluids by HPLC/HPLC-mass spectrometry [14][15][16][17][18][19], by radian compression technique [20].…”
Section: Introductionmentioning
confidence: 99%
“…Prodrug strategy, one of the medicinal chemistry drug delivery systems, has been investigated extensively in order to increase the targeting efficiency of drugs to the brain (Anderson, 1996). Previous work of our research group demonstrated that ethanolamine-related structure could effectively improve drug availability in the brain (Zhang et al, 2012). In this study, we introduced N,N-dimethylethanolamine ligand, with active transport function, to FLU and developed novel FLU conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that drugs conjugated with these ligands could significantly enhance their accumulations in the brain after intravenous (i.v.) injection into rats (Zhang et al, 2012). Ethanolamine-related structures are widely found in either endogenous substances including phosphatidylcholine (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation